1985
DOI: 10.1139/e85-207
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature sulphate reduction: biological versus abiological

Abstract: Sulphate is considered to have been a major source of sulphide in strata-bound and stratiform base-metal sulphide deposits. Many of these deposits, however, appear to have been formed at moderate temperatures (<200 °C), which poses the question, By what mechanism(s) was sulphate reduced to sulphide? Two modes of reduction have been established experimentally: (1) catalysis by sulphate-reducing bacteria, which at present is only known to occur below ca. 100 °C; and (2) abiological reduction by ferrous iron o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(78 citation statements)
references
References 36 publications
2
73
0
3
Order By: Relevance
“…These variable δ 34 S values within a micro-scale area are considered to be the evidence of sulfate reduction in sediments during early diagenesis. Dissolved sulfate may have been reduced to sulfide either by an abiological or biological process (Trudinger and Chamber, 1985;Goldhaber and Orr, 1995;Ohmoto and Goldhaber, 1997). Because the Jeerinah samples preserved original sedimentary textures and do not show any features of hydrothermal alteration, abiological (thermochemical) sulfate reduction is unlikely to explain the sulfur isotope heterogeneity shown in Fig.…”
Section: Origin Of Pyrite In the Jeerinah Formation And Activity Of Smentioning
confidence: 97%
“…These variable δ 34 S values within a micro-scale area are considered to be the evidence of sulfate reduction in sediments during early diagenesis. Dissolved sulfate may have been reduced to sulfide either by an abiological or biological process (Trudinger and Chamber, 1985;Goldhaber and Orr, 1995;Ohmoto and Goldhaber, 1997). Because the Jeerinah samples preserved original sedimentary textures and do not show any features of hydrothermal alteration, abiological (thermochemical) sulfate reduction is unlikely to explain the sulfur isotope heterogeneity shown in Fig.…”
Section: Origin Of Pyrite In the Jeerinah Formation And Activity Of Smentioning
confidence: 97%
“…Since then, a range of similar laboratory experiments with sulfate reactants and the control of various physicochemical parameters to simulate geological conditions have been conducted to study TSR processes and better understand the composition of TSR impacted gas reservoirs (Kiyosu, 1980;Trudinger et al, 1985;Kiyosu and Krouse, 1993;Cross et al, 2004;Yue et al, 2005;Ding et al, 2007;Zhang et al, 2007Zhang et al, , 2008aChen et al, 2009;Lu et al, 2010). Notably, MgSO 4 has been shown to rapidly accelerate TSR at relatively low temperatures (<350°C) and without the need for additional reduced sulfur (Gillaizeau and Tang, 2001;Tang et al, 2005;Zhang et al, 2007Zhang et al, , 2008a (Zhang et al, 2007(Zhang et al, , 2008a.…”
Section: Introductionmentioning
confidence: 99%
“…The sample blank might not only be caused by the contaminant sulfur compound but also through thermochemical sulfate reduction (TSR). Machel (2001) and Trudinger et al (1985) have shown that TSR can take place in the presence of a strong reducing agent even at temperatures well below 200°C. Divalent chromium is a strong reducer and the walls of the reaction flask certainly reach temperatures above 100°C.…”
Section: Discussionmentioning
confidence: 99%